Program “KOMPAK” untuk Meningkatkan Kualitas Hidup Ibu Pasien Kanker Anak - Anak Agung Ayu Ratna Paramita; Sofia Retnowati (Faculty of Psychology, Universitas Gadjah Mada, 2019)
Cancer in children affects not only the patient but for the parents. Parents who have a child with cancer, experience psychological burdens manifested in confusion, shock, rejection, exhaustion, anxiety, and worry. If not handled properly, these symptoms will make them experience stress. It can affect their health quality of life and reduce their ability to accompany child with cancer. Whereas parents health condition greatly affect the health condition of patients with cancer. This study aimed to improve the quality of life of parents who have a child with cancer by providing